(Re)configurations: Design Strategies Based on RelationalTransformation - Moncayo Torres, Pedro (Artes: Architecture, Technology and Sustainability, 2026)
This article advances a relational approach to architectural design, understood as a mode of practice that shifts attention away from form and function as primary determinants and towards the organization of spatial, programmatic, and contextual relations. From this standpoint, architecture is conceived less as the production of autonomous objects than as an operative practice capable of establishing, intensifying, reorganizing, and mediating relations within a given system. Within this framework, the article identifies three recurrent strategies in the author’s design practice: micro-interventions, the engagement of pre-existing conditions, and dynamic organisers. These are not presented as typological categories or as sequential stages in the design process, but as operative modes applicable to both new constructions and interventions on inherited structures. Their significance lies in their capacity to reconfigure hierarchies, activate connections, reprogramme existing relations, and produce new articulations within the project as a whole. The discussion is supported by the author’s own diagrammatic production, understood not merely as a representational device but as an analytical instrument. In this sense, the diagrams render recurrent operations legible and demonstrate that form and function emerge as effects of a prior relational organisation.